The Problem of Values and Evaluation in the Process of Family Upbringing – the Selected Issues from the Methodological Perspective - Opozda, Danuta (Paedagogia Christiana, 2016)
This article attempts to outline the problem of values and evaluation from the methodological perspective of family pedagogy. These issues can be conventionally characterised with reference to preliminary establishments, general perspectives of axiology participation in pedagogy as well as the perspectives of narrow phenomena and related analyses. The article is of a rather general character. It constitutes an offer of emphasising certain issues which are worth considering in the analyses of and research on family upbringing. It also aims at focusing others' and, especially beginner researchers' attention on the subject.